2019
DOI: 10.1093/aob/mcz192
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ultrastructural change of chloroplasts in rice mesophyll cells responding to salt stress

Abstract: Background and Aims Excess salinity inhibits the metabolism of various systems and induces structural changes, especially in chloroplasts. Although the chloroplast body seems to swell under salinity stress as observed by conventional transmission electron microscopy, previous studies are limited to 2-D data and lack quantitative comparisons because specimens need to be sliced into ultrathin sections. This study shows three-dimensionally the structural changes in a whole mesophyll cell respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Moreover, the number of plastoglobuli increased, suggesting a function storage of thylakoid components such as lipids, plastohydroquinone, and tocopherols [51]. However, Oi et al (2020) reported that the 3D reconstructed models of whole rice chloroplasts under salt-stress conditions were not swollen but became spherical without increasing their volume as compared to controls [52].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the number of plastoglobuli increased, suggesting a function storage of thylakoid components such as lipids, plastohydroquinone, and tocopherols [51]. However, Oi et al (2020) reported that the 3D reconstructed models of whole rice chloroplasts under salt-stress conditions were not swollen but became spherical without increasing their volume as compared to controls [52].…”
Section: Discussionmentioning
confidence: 98%
“…Swelling of thylakoids under salt stress (~200 mM NaCl) was reported in rice [50]. However, recent 3D analysis confirmed that rice chloroplasts became spherical under salt stress without any changes in the overall chloroplast volume [51]. Contrasting observations regarding chloroplast volume have been reported among different species.…”
Section: Changes In Ultrastructure Of Chloroplasts In Glycophytes and Halophytesmentioning
confidence: 91%
“…Eventually, there will be a disruption of the cellular membranes and cell homeostasis is eventually derailed. Under salinity stress, plants demonstrate various anatomical changes as seen in chloroplasts such as oval and expanded mesophyll cells compared to the elongated shape in unstressed leaf tissue (Oi et al 2020). Therefore, chloroplasts no longer remain swollen during salt toxicity which affects water turgor pressure.…”
Section: Introductionmentioning
confidence: 99%